THU0096 Multi-biomarker disease activity (MBDA) is associated with the progression of structural bone damage in rheumatoid arthritis patients in remission. (15th June 2017) - Schett, G; Finzel, S; Hagen, M; Englbrecht, M; Haschka, J; Figuereido, C; Cobra, J Fogagnolo; Rech, J
Abstract : Background: Due to an increasing number and an earlier use of effective disease modifying anti-rheumatic drug (DMARD) therapy a growing number of rheumatoid arthritis (RA) patients reaches a state of clinical remission of disease. Whether clinical remission completely protects from structural bone damage, however, is still a matter of debate as conventional radiographic methods have their limitation in the sensitivity to characterize bone damage. Furthermore, residual activity of inflammation associated with the generation of inflammatory markers may characterize a subset of RA patients in remission, associated with higher prevalence and/or progression of bone damage. Objectives: To test whether residual systemic inflammation is associated with structural bone damage and the progression of structural bone damage in RA patients in sustained remission. Methods: RA patients (i) fulfilling the 2010 EULAR/ACR classification criteria of RA, (ii) having a positive anti-citrullinated protein antibody (ACPA) status and (iii) being in DAS28-ESR remission for 6 months were included. High-resolution peripheral quantitative computed tomography (HR-pQCT) of the right hand was done at baseline and after 1year. Erosion numbers and erosion volumes were assessed in the metacarpophalangeal joints. Vectra-DA tests measuring the serum levels of twelve different inflammation markers (CRP, SAA, IL-6, TNFR1, MMP-1, MMP-3, EGF, VEGF-A, VCAM-1, YKL-40, leptin and resistin) were performed in the baseline samples. MBDA score was calculated according to previously defined algorithms with low MDBA score defined as <30 units and moderate to high scores as ≥30 units (1). Results: 100 ACPA+ RA patients in sustained remission were investigate (mean±SD age: 57±14 ys; disease duration: 4.8±4.9 ys; DAS28: 1.7±0.5;63% females; 100% MTX treatment, 38% MTX+TNFi treatment). 65 patients had low (<30), 25 patients has moderate (≥30–44 and 10 patients had high (>44) MBDA scores. Patients in the different MBDA categories had similar age, sex, disease duration, DAS28 scores and DMARD treatment. Baseline HR-pQCT analysis showed that erosion numbers and volumes were significantly (p<0.001) higher in patients with high MBDA scores. Higher erosion numbers (>10) and larger erosions (>10 mm 3 ) were exclusively found in patients with moderate to high MBDA scores. MBDA scores were correlated to erosion numbers (p<0.001) and volumes (p=0.0018). Longitudinal analysis showed significant progression of erosions only in patients with high MBDA scores. Furthermore, progression (>5mm 3 increase in volume) over 1 year was confined to methotrexate treated patients, while tumor necrosis factor inhibitor treated patients were protected from progression even in case of moderate to high MBDA scores. However there were only 4 patients treated with TNFi that had a high MBDA score. Conclusions: These data show that residual disease activity assessed by MBDA score is associated with structural damage and progression of structural damage in RA patients in sustained remission. References: Curtis JR, van der Helm-van Mil AH, Knevel R, et al.Validation of a novel multi-biomarker test to assess rheumatoid arthritis disease activity. Arthritis Care Res 2012;64:1794–803. Disclosure of Interest: None declared